(untitled) (Socio-economic relations in the digital society, 2019)
The paper proposes modern tools of unsteady dynamic processes researching methods to measure and analyze commercial banks indicators such as using models phase plane, which consists in construct the phase portrait of the system and further analysis of this portrait. It makes possible on the bases of phase trajectories to visualize the set of movements occurring in the system for diff erent initial conditions and co-integration models for predicting that reflect the interaction of processes linked non-stationary long-term relationships. Such indicators as total financial result, total loans volume and deposits of the banking system are investigated for building the complex of models for researching of dynamics of Ukraine banking system stability. The models of assessment and analysis of these indicators interaction are built on the bases of econometric tools in the following way: the model of total financial result and total credit; model of total financial result and total deposits; model of total loans and deposits. Analysis of the results of predictive models makes possible to conclude that at this stage of economic development, the banking system is unstable, trajectories are oscillating periodic or aperiodic character, therefore, insufficient stability of the system leads to increased negative impact of external factors, which may eventually give it increasingly strong influence that could lead to catastrophic consequences. The implementation of instruments for research the dynamics of indicators interaction on the bases of proposed dynamic models will determine the strategy of stabilization and further development of the banking system, quality status of which is determined by close relationships induction of major financial and economic indicators that describe the real system state.